Pyruvate dehydrogenase kinase as a novel therapeutic target in oncology - Sutendra, Gopinath; Michelakis, Evangelos D. (Frontiers in Oncology, 2013)
Current drug development in oncology is non-selective as it typically focuses on pathways essential for the survival of all dividing cells. The unique metabolic profile of cancer, which is characterized by increased glycolysis and suppressed mitochondrial glucose oxidation provides cancer cells with a proliferative advantage, conducive with apoptosis resistance and even increased angiogenesis. Recent evidence suggests that targeting the cancer-specific metabolic and mitochondrial remodeling may offer selectivity in cancer treatment. Pyruvate dehydrogenase kinase (PDK) is a mitochondrial enzyme that is activated in a variety of cancers and results in the selective inhibition of pyruvate dehydrogenase (PDH), a complex of enzymes that converts cytosolic pyruvate to mitochondrial acetyl-CoA, the substrate for the Krebs’ cycle. Inhibition of PDK with either small interfering RNAs or the orphan drug dichloroacetate (DCA) shifts the metabolism of cancer cells from glycolysis to glucose oxidation and reverses the suppression of mitochondria-dependent apoptosis. In addition, this therapeutic strategy increases the production of diffusible Krebs’ cycle intermediates and mitochondria-derived reactive oxygen species (mROS), activating p53 or inhibiting pro-proliferative and pro-angiogenic transcription factors like nuclear factor of activated T-cells (NFAT) and hypoxia-inducible factor 1α (HIF1α). These effects result in decreased tumor growth and angiogenesis in a variety of cancers with high selectivity. In a small but mechanistic clinical trial in patients with glioblastoma, a highly aggressive and vascular form of brain cancer, DCA decreased tumor angiogenesis and tumor growth, suggesting that metabolic targeting therapies can be translated directly to patients. Therefore, reversing the mitochondrial suppression with metabolic-modulating drugs, like PDK inhibitors holds promise in the rapidly expanding field of metabolic oncology.